2008
DOI: 10.1002/eco.32
|View full text |Cite
|
Sign up to set email alerts
|

Relating streamflow characteristics to specialized insectivores in the Tennessee River Valley: a regional approach

Abstract: Analysis of hydrologic time series and fish community data across the Tennessee River Valley identified three hydrologic metrics essential to habitat suitability and food availability for insectivorous fish communities in streams of the Tennessee River Valley: constancy (flow stability or temporal invariance), frequency of moderate flooding (frequency of habitat disturbance), and rate of streamflow recession. Initial datasets included 1100 fish community sites and 300 streamgages. Reduction of these datasets t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 63 publications
1
57
0
Order By: Relevance
“…A large number of endemic fish species and a unique assemblage of mussels, crayfish, and salamanders make the Tennessee River basin an excellent area for ecohydrological studies (Abell et al, 2000). From a study published by Knight et al (2008), 25 catchments in the Tennessee River basin with observed streamflow time series (U.S. Geological Survey, 2016b), pre-cipitation (U.S. Department of Commerce, 2007a), temperature (U.S. Department of Commerce, 2007b), and potential evaporation data (Rotstayn et al, 2006) were selected. The catchment areas range between 100 and 4800 km 2 with elevations ranging from 174 to 937 m (U.S. Geological Survey, 2016a).…”
Section: Catchment Locations and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of endemic fish species and a unique assemblage of mussels, crayfish, and salamanders make the Tennessee River basin an excellent area for ecohydrological studies (Abell et al, 2000). From a study published by Knight et al (2008), 25 catchments in the Tennessee River basin with observed streamflow time series (U.S. Geological Survey, 2016b), pre-cipitation (U.S. Department of Commerce, 2007a), temperature (U.S. Department of Commerce, 2007b), and potential evaporation data (Rotstayn et al, 2006) were selected. The catchment areas range between 100 and 4800 km 2 with elevations ranging from 174 to 937 m (U.S. Geological Survey, 2016a).…”
Section: Catchment Locations and Characteristicsmentioning
confidence: 99%
“…Thirteen SFCs assessed in this study were chosen for use in model scenarios based on discernible functional connections with fish community diversity (Knight et al, 2008(Knight et al, , 2014. This set of 13 SFCs represents each of the major flow regime components commonly used in ecological studies (e.g., Olden and Poff, 2003;Arthington et al, 2006;Caldwell et al, 2015): magnitude, ratio, frequency, variability, and date (Table 1).…”
Section: Selection Of Sfcsmentioning
confidence: 99%
“…In this study, the overall flow regime was divided into high, middle and low flow events based on the daily flow duration curve and was characterized by 16 flow metrics including magnitude (5), frequency and variation (3), duration (3), timing (2) and rating (3) of flow events (Richter et al, 1996;Olden and Poff, 2003;Poff et al, 1997Poff et al, , 2010aKnight et al, 2008Knight et al, , 2012Kennard et al, 2010) (Table 1). All the 16 observed and simulated metric values were extracted from the observed and simulated daily streamflow series in the entire period (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005), respectively.…”
Section: Flow Regime Metrics and Evaluation Criteriamentioning
confidence: 99%
“…It is widely accepted that flow regimes play a critical role in flood control, domestic and production water supply (Bauwens and Vandewiele, 1989;Lehner et al, 2006), migration and transformation processes of nutrients (Poff et al, 1997;Ahmet et al, 2006;van Griensven and Meixner, 2007), variation of species habitat, as well as biodiversity and life history patterns in aquatic ecosystems (Poff et al, 1997;Bunn and Arthington, 2002;Knight et al, 2008;Arthington et al, 2010). Except for the traditional resource attribute of flow regimes, their environmental and ecological attributes were gradually paid more attention.…”
Section: Flow Regimes and Water Resources Managementmentioning
confidence: 99%
See 1 more Smart Citation